2010
DOI: 10.1007/s10900-010-9234-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Incarceration a Contributor to Health Disparities? Access to Care of Formerly Incarcerated Adults

Abstract: Despite the disproportionate prevalence of incarceration in communities of color, few studies have examined its contribution to health disparities. We examined whether a lifetime history of incarceration is associated with recent access to medical and dental care. We performed a secondary data analysis of the 2007 Los Angeles County Health Survey, a population-based random-digit-dialing telephone survey of county households. Any history of incarceration in a prison/jail/detention center as an adult was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 14 publications
4
99
0
Order By: Relevance
“…However, previous research, as well as the current study, has demonstrated that these barriers remain (Kulkarni, et al, 2010;Douds et al, 2016). This calls for a collaborative effort engaging correctional and community stakeholders to bridge access and service gaps along the current dental care continuum for those incarcerated in Georgia.…”
Section: Public Health Implicationsmentioning
confidence: 46%
See 2 more Smart Citations
“…However, previous research, as well as the current study, has demonstrated that these barriers remain (Kulkarni, et al, 2010;Douds et al, 2016). This calls for a collaborative effort engaging correctional and community stakeholders to bridge access and service gaps along the current dental care continuum for those incarcerated in Georgia.…”
Section: Public Health Implicationsmentioning
confidence: 46%
“…The ability of a dental provider to identify and treat an oral health condition that can be detected only by a thorough clinical examination is hindered when preventive visits are not maintained. In addition, despite an individual's desire to seek appropriate care, timely treatment may still be impeded by the social and economic challenges of not having a primary dental provider, lack of adequate insurance coverage, and other financial restrictions (Kulkarni et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all types of health services, particularly in rural settings, individuals face difficulty locating and receiving services in response to their health care needs ( Kulkarni, Baldwin, Lightstone, Gelberg, & Diamant, 2010). A combination of demographic and community factors (including minority status, poverty, low numbers of health services providers, and lack of outreach by community health programs) often limit access to health and mental health services ( Dumont, Brockmann, Dickman, Alexander, & Rich, 2012;Owens, Rogers, & Whitesell, 2011).…”
Section: Service Access For Rural Adultsmentioning
confidence: 99%
“…Previous incarceration has been independently linked to increased rates of chronic disease and poor health care access for both genders [7,8]. However, incarcerated women have significantly higher rates of asthma, hypertension, diabetes, cancer, arthritis, hepatitis, and cirrhosis as well as depression, bipolar disorder, posttraumatic stress, anxiety, personality disorders, and drug abuse compared to incarcerated men [9].…”
Section: Introductionmentioning
confidence: 99%